Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Time and Space Optimized Storage-based BIST under Multiple Voltages and Variations - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Test Symposium, The Hague, Netherlands, May 20-24, 2024)

Vmin Testing under Variations: Defect vs. Fault Coverage - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Latin American Test Symposium (LATS), Maceió, Brazil, April 9-12, 2024)

Functional Safety and Reliability of Interconnects throughout the Silicon Life Cycle - Hellebrand, Sybille; Sadeghi-Kohan, Somayeh; Wunderlich, Hans-Joachim (International Symposium of EDA (ISEDA), Xi'an, China, May 10-13, 2024)

Involvement of domain experts in the AI training does not affect adherence – An AutoML study - Lebedeva, Anastasia; Protte, Marius; van Straaten, Dirk; Fahr, René (Advances in Information and Communication)